REGULATORY FEATURES OF CHILD AND YOUTH TOURISM REGULATION: NATIONAL AND INTERNATIONAL EXPERIENCE - Tsokur, Elena; Stepanova, Diana; Neymyshev, Alexey; Allanina, Liliya; Dyakonov, Mikhail (Revista Inclusiones, 2020)
The article defines the features of legal regulation of relations in the field of child and youth tourism in the countries of the world. Child tourism is one of the most important directions of the tourism industry, as well as one of the priorities of the state policy in the field of education of future generations. The development of child tourism is hindered by insufficient legal regulation, and the problems of its accessibility and ensuring proper security remain unresolved. The purpose of this work is to develop and present options for improving the current legislation to regulate child tourism, which is adequate to the current situation and contributes to solving existing problems.